Inflammatory microRNAs in cardiovascular pathology: another brick in the wall - Zapata-Martínez, Laura; Águila, Sonia; de los Reyes-García, Ascensión M.; Carrillo-Tornel, Salvador; Lozano, María L.; González-Conejero, Rocío; Martínez, Constantino (Frontiers in Immunology, 2023)
The regulatory role of microRNAs (miRNAs) is mainly mediated by their effect on protein expression and is recognized in a multitude of pathophysiological processes. In recent decades, accumulating evidence has interest in these factors as modulatory elements of cardiovascular pathophysiology. Furthermore, additional biological processes have been identified as new components of cardiovascular disease etiology. In particular, inflammation is now considered an important cardiovascular risk factor. Thus, in the present review, we will focus on the role of a subset of miRNAs called inflamma-miRs that may regulate inflammatory status in the development of cardiovascular pathology. According to published data, the most representative candidates that play functional roles in thromboinflammation are miR-21, miR-33, miR-34a, miR-146a, miR-155, and miR-223. We will describe the functions of these miRNAs in several cardiovascular pathologies in depth, with specific emphasis on the molecular mechanisms related to atherogenesis. We will also discuss the latest findings on the role of miRNAs as regulators of neutrophil extracellular traps and their impact on cardiovascular diseases. Overall, the data suggest that the use of miRNAs as therapeutic tools or biomarkers may improve the diagnosis or prognosis of adverse cardiovascular events in inflammatory diseases. Thus, targeting or increasing the levels of adequate inflamma-miRs at different stages of disease could help mitigate or avoid the development of cardiovascular morbidities.